SOFTWARE DEVELOPMENT FOR PLAYING VIRTUAL REALITY - Tursunov , Muhriddin Muhammad ugli (Educational Research in Universal Sciences, 2023)
The paper analyzes methods of filtering data obtained from an inertial measuring device, methods of overcoming the zero drift of a gyroscope, developed a stereoscopic rendering program for a mobile phone and a wireless inertial manipulator. Which allows users to immerse themselves in the world of virtual reality for a small amount. Selected data filtering methods allow you to automatically collect, filter, and smooth data of almost any kind.